Implementasi Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IV.A Mata Pelajaran IPAS di SDN 4 Palembang - Selviah, Fitri; Kifitah, Maryatul; Hasmawati, Hasmawati; Wulandari, Irma; Ismet, Ismet; Rodzikin, Khoirul; Wiranto, M.; Wati, Ety Madya (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to improve the learning outcomes of students in the subject of Natural and Social Sciences (IPAS) in class IV.A at SD Negeri 4 Palembang through the implementation of the Problem Based Learning (PBL) model. The research method used is Classroom Action Research (CAR) conducted in two cycles, with a total of 31 students as the subjects. Data were collected through observations, tests, and documentation to evaluate the effectiveness of the applied learning model. The results indicate that the implementation of the PBL model significantly enhances student engagement and learning outcomes, where only 12 out of 31 students met the Minimum Completeness Criteria (KKM) in the initial evaluation, which improved significantly after the model was applied. This research contributes to the development of relevant and contextual teaching methods and supports the implementation of the Merdeka Curriculum in Indonesia.